Effects of an Instant Response System integrated learning activity on EFL students' learning achievement and perceptions. (December 2021) - Chang, Ching
Abstract: A growing body of evidence supports the effectiveness of instant response systems (IRSs) in fostering learning, but related studies in foreign language education are scarce. This study aims to fill this gap by examining the efficacy of IRS question-and-answer learning activities in the context of large English as a foreign language (EFL) classes for beginner students with elementary-level English proficiency. A series of question-and-answer activities based on IRS using the peer instruction (PI) is created for helping students promote their learning. A total of 102 university students participated in a quasi-experiment; 52 were assigned to an experimental group and learnt with an IRS-integrated activity, while 50 were in a control group and learnt with a non-IRS activity. The data were gathered using an achievement assessment instrument, a perception questionnaire, and individual interviews. The collected data were then analysed to examine students' learning achievements and learning perceptions. Results show that IRS can effectively promote students' learning, and foster positive perceptions of learning. Future implementations on IRS-integrated learning activities are thus recommended for educators.